2018
DOI: 10.1101/404590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmark Problems for Dynamic Modeling of Intracellular Processes

Abstract: Motivation: Dynamic models are used in systems biology to study and understand cellular processes like gene regulation or signal transduction. Frequently, ordinary differential equation (ODE) models are used to model the time and dose dependency of the abundances of molecular compounds as well as interactions and translocations. A multitude of computational approaches have been developed within recent years. However, many of these approaches lack proper testing in application settings because a comprehensiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 46 publications
(35 reference statements)
0
40
0
Order By: Relevance
“…As the performance of optimization algorithms has so far mostly been evaluated for ODE models with tens and hundreds of unknown parameters (Villaverde et al, 2018;Hass et al, 2019), we used our results for a first comparison on a large-scale ODE model. We found that for the considered problem (i) Ceres always stopped prematurely, (ii) sumsl progressed (at least for the standard optimization) slower than Ipopt and fmincon, and (iii) fmincon and Ipopt reached the best objective function values and appeared to be most efficient ( Figure 3A, B).…”
Section: Normalization Results In Information Lossmentioning
confidence: 99%
“…As the performance of optimization algorithms has so far mostly been evaluated for ODE models with tens and hundreds of unknown parameters (Villaverde et al, 2018;Hass et al, 2019), we used our results for a first comparison on a large-scale ODE model. We found that for the considered problem (i) Ceres always stopped prematurely, (ii) sumsl progressed (at least for the standard optimization) slower than Ipopt and fmincon, and (iii) fmincon and Ipopt reached the best objective function values and appeared to be most efficient ( Figure 3A, B).…”
Section: Normalization Results In Information Lossmentioning
confidence: 99%
“…In this study, we considered application examples for which quantitative measurements are available and which are included in a collection of benchmark problems for parameter estimation, which facilitates easy reusability (Hass et al, 2019). This enables a comparison of parameter estimation using quantitative and qualitative data.…”
Section: Test Problemsmentioning
confidence: 99%
“…The small-to medium-scale examples for the benchmark study were chosen based on a collection of benchmark models (20). We chose models with different system sizes, which allowed the generation of large artificial datasets, which were sufficiently heterogeneous.…”
Section: Adaptation Of Benchmark Models and Creation Of Artificial Datamentioning
confidence: 99%